POTENTIAL, PROBLEMS, AND DIRECTION OF DEVELOPMENT OF THE GALANG ISLAND TOURISM AREA (Pena Cendekia Insani, 2026)
Galang Island possesses potential for historical, marine, and cultural tourism, but its management still faces challenges related to access, infrastructure, and the protection of local identity. This study analyzes existing conditions and offers development directions based on conservation, community empowerment, and integrated promotion. The findings recommend cross-sector synergy and the implementation of sustainable tourism to support ecological, economic, and cultural balance.